2015
DOI: 10.1021/acscatal.5b00949
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Non-Leloir Furanose-Transferring Enzymes from an α-l-Arabinofuranosidase: A Rationale for the Engineering of Evolved Transglycosylases

Abstract: The vast biodiversity of glycoside hydrolases (GHs) constitutes a reservoir of readily-available carbohydrateacting enzymes that employ simple substrates and hold the potential to perform highly stereopecific and regioselective glycosynthetic reactions. However, most GHs preferentially hydrolyze glycosidic bonds and are thus characterized by a hydrolysis/transglycosylation partition in favor of hydrolysis. Unfortunately, current knowledge is insufficient to rationally modify this partition, specifically mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 70 publications
6
72
0
Order By: Relevance
“…They hypothesized that the reduced interactions destabilize the transition states of the reaction, which affects hydrolysis more than transglycosylation and thereby improves the ratio of transglycosylation. The same effect has been seen in several other mutational studies (Arab-Jaziri et al 2015; Aronson et al 2006; Bissaro et al 2015a; Feng et al 2005). …”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…They hypothesized that the reduced interactions destabilize the transition states of the reaction, which affects hydrolysis more than transglycosylation and thereby improves the ratio of transglycosylation. The same effect has been seen in several other mutational studies (Arab-Jaziri et al 2015; Aronson et al 2006; Bissaro et al 2015a; Feng et al 2005). …”
Section: Introductionsupporting
confidence: 81%
“…A stronger nucleophile acceptor may not require this acid catalysis. Furthermore, several mutational studies have indicated the involvement of this tyrosine in modulating the preference for transglycosylation (Bissaro et al 2015a; Teze et al 2014).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies aimed at improving transglycosylation in rGHs, 14,16,17,[50][51][52][53][54] it is well-established that mutations that lower the hydrolytic component of the reaction and others that increase acceptor binding can lead to overall improvements in transglycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the key molecular determinants that differentiate TGs from hydrolytic GHs are still unclearly defined, despite considerable efforts to discover these and relevant studies on reversed transglycosylation/hydrolysis (T/H) partition. [12][13][14][15][16][17] The class of GHs (retaining GHs, hereafter referred to as rGHs) mostly holding the potential to perform transglycosylation reactions are those that catalyze the hydrolysis of glycosidic bonds through a double displacement mechanism that results in the retention (in the product) of the configuration of the anomeric carbon originally present in the donor substrate. The reaction trajectory of rGHs is characterized by the formation of a more or less transient glycosylated enzyme reaction intermediate that can be deglycosylated either by a water molecule (hydrolysis), or by another suitable acceptor moiety (transglycosylation), including sugars and alcohols ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%